Effects of COVID -19 on women’s mental health: A systematic review (2022)
Women are part of the first line of care not only in the healthcare field but also in the care economy, which is why they tend to be more susceptible to distress due to infection amid a pandemic, triggering mental health consequences that could extend into the long term, even after the end of the pandemic. To present findings on the mental health effects on women during the period of the COVID-19 pandemic, a systematic review is presented that shows an increase in symptoms associated with depression, anxiety, and post-traumatic stress in women, as well as problems of insomnia and stress in female healthcare professionals due to direct contact with suspected or confirmed cases of COVID-19. Identifying vulnerable groups amid the pandemic and investing efforts in improving the physical and psychological well-being of this population would reduce chronic mental health problems in the general population, given that women tend to be the support of families and society.